1910 Mass. Acts 552, An Act to Prohibit the Sale of Certain Pistols and Explosives and to Authorize the Making of Regulations Relative to Fireworks and Firecrackers, ch. 565, § 1. - (:unkn) unknown (General Publisher, 1910)
It shall be unlawful for any person to sell or keep for sale any blank cartridge, toy pistol, toy gun or toy cannon that can be used to fire a blank cartridge; or to sell or keep for sale, or to fire, explode or cause to explode any blank cartridge or bomb; or to sell or keep for sale, or to set off, explode or cause to explode any fireworks containing any pieric acid or pierates, or any firecracker exceeding two inches in length and three eights of an inch in diameter or of a greater explosive power than a firecracker of such size containing black gunpowder only . . .
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES